2014
DOI: 10.1002/ccd.25357
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility and safety of a virtual 3‐Fr sheathless‐guiding system for percutaneous coronary intervention

Abstract: PCI using the virtual 3-Fr system is a feasible and viable alternative to conventional procedures that use a sheath and GC in appropriately selected patients. This small-caliber system may minimize endovascular trauma, particularly during transradial coronary procedures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 23 publications
0
6
0
Order By: Relevance
“…A total of 66 studies met the inclusion criteria . The process of study selection is shown in Figure .…”
Section: Resultsmentioning
confidence: 99%
“…A total of 66 studies met the inclusion criteria . The process of study selection is shown in Figure .…”
Section: Resultsmentioning
confidence: 99%
“…The 5 Fr sheathless guiding catheter (Medikit Co., Ltd) is advanced using a specialised insertion system. Use for treatment of complex coronary artery disease has been described in detail 23 . Successful treatment of CTO lesions has been shown to be possible with this system 24 , and a recent case report showed that a 4 Fr guiding catheter (KIWAMI, Heartrail; Terumo Corp.) can be inserted into the 5 Fr guiding catheter to improve stent delivery 25 .…”
Section: Sheathless Techniques Sheathless Systemsmentioning
confidence: 99%
“…Recently, Tonomura et al reported on 132 consecutive patients who underwent PCI using this system 23 . The procedural success rate was 95%.…”
Section: Sheathless Techniques Sheathless Systemsmentioning
confidence: 99%
“…Mizuno et al reported success in 24/27 cases with crossover to conventional 6F in three cases, and more recently Kurotobi et al reported procedural success in 126/132 selected cases of simple PCI with cross-over to conventional PCI in six cases [31,32]. These studies therefore show that the diminutive 5F sheathless system from MediKit is successful for simple PCI with a very small outer diameter equivalent to a 3F sheath.…”
Section: Medikit Work Sheathless Guide Systemmentioning
confidence: 76%